The coexistence of race and racism can they become extinct together? - Hutchinson, Janis Faye 1953- (University Press of America, 2005)
Race and racism are interconnected historically and in the modern world. This connection is related to changing social, political, and economic conditions that impact how we think of others and ourselves. Race and racism are also connected to biological discoveries that justified how we think of others and ourselves. The main focus of this book is the examination of these connections. It is argued that while both race and racism are social constructions, the justification for racism changed as the definition and attributes of races were modified to correspond new developments in biology and genetics.